Rediscovered after Nearly a Century: The Silvery Pigeon Columba argentina ( Columbiformes: Columbidae) on Natuna Island, Sumatra, Indonesia - Syah Abdul Hakim; Ahdiani; Muhammad Iqbal (BIO PALEMBANICA, 2025)
The Silvery Pigeon Columba argentina, a Critically Endangered species endemic to Indonesia, was long thought to be possibly extinct, with confirmed records limited to a few offshore islands west of Sumatra. Here, we report the rediscovery of C. argentina on Natuna Island, Riau Islands Province, Sumatra, Indonesia, representing the first confirmed record from this locality since 1928, nearly a century ago. Field observations and photographs obtained in July 2023 and May 2024 confirm the species' continued survival in coastal and lowland habitats on Natuna Island. This rediscovery extends the known current range of C. argentina beyond the western offshore islands of Sumatra and provides crucial evidence that remnant populations persist in the Riau Islands. This finding underscores the significance of Natuna Island and surrounding areas for the conservation of C. argentina.